Schistosoma mansoni: protective immunity in mice cured by chemotherapy at the chronic phase of the disease Schistosoma mansoni: imunidade protetora em camundongos curados por quimioterapia na fase crônica da doença - Fernando Schemelzer de Moraes Bezerra; Paulo Marcos Zech Coelho; Carlos Alberto Pereira Tavares (Revista do Instituto de Medicina Tropical de São Paulo, 1993)
Aiming at demonstrating a decrease of acquired immunity after chemotherapeutic cure, a group of mice was infected with 25 Schistosoma mansoni cercariae (LE strain). A part of these animals was treated with 400 mg/kg oxamniquine, at 120 days after infection. Challenge infections were carried out at 45, 90 and 170-day-intervals after treatment (185, 210 and 290 days after primoinfection, respectively). Recovery of worms at 20 days after reinfections showed that a residual immunity remains up to 90 days after treatment, and disappears at 170 days after cure. Using the ELISA method, it was possible to detect a decrease of antibody levels (total IgG) in the treated group, when antigens from different evolutive stages of S. mansoni were used. The epidemiological implications of the present results, and the possible mechanisms involved in the decrease of acquired immunity after treatment are discussed. Para evidenciar a queda da imunidade adquirida após cura quimioterápica, um lote de camundongos foi infectado com ±25 cercárías de S. mansoni (cepa LE). Parte destes animais foi tratada aos 120 dias com 400 mg/kg de oxamniquina. Foram feitos desafios em intervalos de 45, 90 e 170 dias após o tratamento (185, 210 e 290 dias após a primoinfecção, respectivamente). A recuperação aos 20 dias após as infecções desafio, dos vermes das reinfecções mostrou que a imunidade residual persiste até os 90 dias após o tratamento e desaparece aos 170 dias após a cura. Com o soro dos camundongos, através do método de ELISA, evidenciou-se uma queda nos níveis de anticorpos (IgG total) no grupo tratado em relação a vários antígenos de estágios evolutivos do S. mansoni. As implicações epidemiológicas dos presentes resultados e os possíveis mecanismos envolvidos na queda da imunidade adquirida após tratamento são discutidos.